8 1 sin 2 x + 8 1 cos 2 x = 3 0
If A and B are the two values of x ∈ [ 0 , 2 π ] such that the equation above is fulfilled, find the value of A + B π .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Multiply Both sides by 8 1 c o s 2 x ⟹ 8 1 s i n 2 x + c o s 2 x + 8 1 2 c o s 2 x = 3 0 × 8 1 c o s 2 x = 8 1 + 8 1 2 c o s 2 x = 3 0 × 8 1 c o s 2 x Put 8 1 c o s 2 x = y ⟹ 8 1 + y 2 = 3 0 y = y 2 − 3 0 y + 8 1 = 0 = y 2 − 2 7 y − 3 y + 8 1 = 0 = ( y − 2 7 ) ( y − 3 ) = 0 ⟹ 8 1 c o s 2 x = 2 7 , 3 = 3 4 c o s 2 x = 3 3 , 3 1 c o s 2 x = 4 3 , 4 1 x = 6 π , 3 π
Superb! (+1)
Log in to reply
Long time no talk 😃
Log in to reply
Yes, I dont come here much now, though i do maintain my streak :P
8 1 sin 2 x + 8 1 cos 2 x = 3 0 Let cos 2 x = a ⟹ sin 2 x = 1 − a ∴ 8 1 sin 2 x + 8 1 cos 2 x = 3 0 8 1 1 − a + 8 1 a = 3 0 8 1 1 × 8 1 − a + 8 1 a = 3 0 8 1 a 8 1 + 8 1 a = 3 0 8 1 a 8 1 + 8 1 2 a = 3 0 8 1 + 8 1 2 a = 3 0 × 8 1 a 8 1 2 a − 3 0 × 8 1 a + 8 1 = 0 Let 8 1 a = x ⟹ ( 8 1 x ) 2 − 3 0 × 8 1 a + 8 1 = 0 x 2 − 3 0 x + 8 1 = 0 x 2 − 3 x − 2 7 x + 8 1 = 0 x ( x − 3 ) − 2 7 ( x − 3 ) = 0 ( x − 2 7 ) ( x − 3 ) = 0 x = 2 7 , x = 3 ⟹ 8 1 a = 2 7 , 8 1 a = 3 ( 3 4 ) a = 3 3 , ( 3 4 ) a = 3 3 4 a = 3 3 , 3 4 a = 3 4 a = 3 , 4 a = 1 ∴ sin 2 x = 4 3 , sin x = 4 1 ⟹ sin x = 4 3 , sin x = 2 1 ⟹ x = 6 0 , x = 3 0 A = 3 π ; B = 6 π Therefore, the answer is 3 π + 6 π π = 0 . 5 π π = 2
Good, but you could've used fewer steps. Also, in the 5th step from the bottom, change the sin x to sin x .
See a shorter version below (my solution).
Also, it is not recommended to use the same variable (in this case: x) for two different expressions within the same solution.
(e.g. "Let 8 1 a = y " would have been much better, than "Let 8 1 a = x ")
8 1 s i n 2 x + 8 1 c o s 2 x = 3 0
8 1 s i n 2 x + 8 1 1 − s i n 2 x = 3 0
8 1 s i n 2 x + 8 1 s i n 2 x 8 1 = 3 0
Let y = 8 1 s i n 2 x
Then:
y + y 8 1 = 3 0
y 2 − 3 0 y + 8 1 = 0
( y − 3 ) ( y − 2 7 ) = 0
y = 3 or y = 27
Substituting these values back into
y = 8 1 s i n 2 x = 3 4 s i n 2 x
we get:
sin x = ± 2 3 or sin x = ± 2 1
and solving it for 0 ≤ x ≤ 2 π
A = 3 π
B = 6 π
Hence,
A + B π = 3 π + 6 π π = 2 π π = 2
Problem Loading...
Note Loading...
Set Loading...
8 1 sin 2 x + 8 1 cos 2 x 8 1 sin 2 x + 8 1 1 − sin 2 x 8 1 sin 2 x + 8 1 sin 2 x 8 1 y + y 8 1 ⟹ y 2 − 3 0 y + 8 1 ( y − 3 ) ( y − 2 7 ) = 3 0 = 3 0 = 3 0 = 3 0 = 0 = 0 Let y = 8 1 sin 2 x
⟹ { y = 3 , y = 2 7 , 8 1 sin 2 x = 3 4 sin 2 x = 3 1 , 8 1 sin 2 x = 3 4 sin 2 x = 3 3 , 4 sin 2 x = 1 , 4 sin 2 x = 3 , sin x = 2 1 , sin x = 2 3 , x = 6 π = A x = 3 π = B
⟹ A + B π = 6 π + 3 π π = 6 1 + 3 1 1 = 2